Descrição dos primeiros recém-nascidos monitorizados por meio de eletroencefalograma de amplitude integrada em uma maternidade privada do Nordeste do Brasil - Lucas Rocha Barreto de Almeida; Marcos Alves Pavione; Arnon Silva de Carvalho; Gabriel Fernando Todeschi Variane (Residência Pediátrica)
Continuous brain monitoring using amplitude-integrated electroencephalography (aEEG) enables the detection of subclinical seizures and their early treatment, promoting neuroprotection and preventing permanent neurological injuries. The objective of this study was to analyze the profile of newborns (NB) monitored remotely by a team using this methodology in a private maternity hospital in the northeastern region of Brazil. METHODOLOGY: This was an observational, descriptive, and cross-sectional clinical study. A convenience sample was used, including all sequential newborns submitted to neuromonitoring from February 2021 to June 2022. Maternal and clinical data of the NB were collected through a form designed by the researchers and subsequently subjected to descriptive statistical analysis using R Core Team 2022 software (Version 4.2.2). The study was submitted and approved by the Ethics Committee under CAAE 55437521.8.0000.5371. RESULTS: A total of 16 NB were included. The most common indications for aEEG monitoring were suspected seizures (37.5%) and the presence of witnessed clinical seizures (18.75%). During the study, 5 NB (31.25%) could have their anticonvulsant medication discontinued early after aEEG monitoring; 5 NB (31.5%) with suspected clinical seizures had the hypothesis ruled out and did not start anticonvulsant therapy, and in 18.8% (n=3) of patients, subclinical seizures were observed in the examination, leading to the initiation of treatment. CONCLUSION: aEEG allowed the medical team to suspend or avoid the unnecessary use of anticonvulsants in 81.2% of the investigated NB and safely maintain or initiate anticonvulsant therapy in 18.8% of cases.